KONSEPSI BELAJAR DAN MENGAJAR DALAM AL-QUR’AN - Al Firdaus (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2023)
Learning and teaching play a very important role for the future progress of the Indonesian nation. There is still homework to be done by academics regarding this learning. A few days ago there was a commotion between motor gen. This makes a teenager brutal to slash to death another teenager. Another incident, we are sad to witness a teenager who yelled at his teacher. This incident raises many questions about what is wrong with our education system or what academics should do. The Qur'an since it was revealed responds to all existing events. The purpose of learning and teaching in order to illuminate the dark side of human behavior. Therefore humans are ordered to read events in this universe in order to give him a signal that humans without knowledge will lead to destruction. So it is important that this paper discusses the conception of learning and teaching in the Qur'an. So that the Al-Qur'an can provide educational enlightenment to the world of education today. The method used in the assessment is descriptive analysis combined with maudhu'i interpretation. While the data obtained through library research. Which went through three stages of description, comparison, analysis and development which in the end obtained conclusions according to the formulation of the problem and research objectives.